(untitled) (diségno, 2018)
The acquisition of this historical knowledge –according to the purpose of this issue of diségno– should help us to understand what we actually mean when we talk about ‘Geometry’ in the field of university researches especially applied to Design, Pedagogy and Arts schools. In this field, specifically, the history of geometry should not be mistaken for the histories of mathematics [Chasles, 1837, Loria, 1921], or with the history of art and ancient erudition: these general historiographical issues have other (authoritative) scientific and editorial references (read more).